Application of cellulases from an alkalothermophilic thermomonospora sp in biopolishing of denims - Anish, Ramakrishnan; Rahman, Mohammad Safikur; Rao, Mala (Biotechnology and Bioengineering, 2007)
Use of cellulase for denim washing is a standard eco-friendly technique to achieve desirable appearance and softness for cotton fabrics and denims. But enzymatic washing of denim till date involved acid cellulase (Trichoderma reesei) and neutral cellulase (Humicola isolens) the use of which has a drawback of backstaining of the indigo dye on to the fabric. Though it has been suggested that pH is a major factor in controlling backstaining there are no reports on use of cellulase under alkaline conditions for denim washing. In this study for the first time an alkali stable endoglucanase from alkalothermophilic Thermomonospora sp. (T-EG) has been used for denim biofinishing under alkaline conditions. T-EG is effective in removing hairiness with negligible weight loss and imparting softness to the fabric. Higher abrasive reactivity with lower backstaining was a preferred property for denim biofinishing exhibited by T-EG. The activities were comparable to acid and neutral cellulases that are being regularly used. The enzyme was also effective under non-buffering conditions which is an added advantage for use in textile industry. A probable mechanism of enzymatic finishing of cotton fabric has been represented based on the unique properties of T-EG.
Keywords: alkaline conditions; biopolishing; Cellulase; denim; Thermomonospora sp